Revision of the spider genera Nilus O. Pickard-Cambridge 1876, Sphedanus Thorell 1877 and Dendrolycosa Doleschall 1859 (Araneae: Pisauridae) - Jäger, Peter (Zootaxa, 2011)
The genera Nilus O. Pickard-Cambridge 1876, Sphedanus Thorell 1877 and Dendrolycosa Doleschall 1859 are revised. Nilus is recognised as junior synonym of Thalassius Simon 1885; accordingly all species previously placed in Thalassius including nomina dubia are transferred to Nilus. Nilus curtus O. Pickard-Cambridge 1876 is recognised as senior synonym of Thalassius spinosissimus Karsch 1879. Nilus decoratus (Patel & Reddy) comb. nov. from India is transferred from Pisaura Simon 1885. Nilus amazonicus Simon 1898 from Brazil is transferred to the genus Architis Simon 1898: Architis amazonica (Simon 1898) comb. nov. Nilus oblongus Pavesi 1897 from Ethiopia and N. marginatus (Simon 1888) from the Andaman Islands are considered nomina dubia. Sphedanus Thorell 1877 is removed from the synonymy with Nilus and recognised as a senior synonym of Eurychoera Thorell 1897. The type species, S. undatus Thorell 1877, is redecribed and its copulatory organs are illustrated for the first time. Two species previously placed in the genus Eurychoera are transferred: Sphedanus banna (Zhang, Zhu & Song 2004) comb. nov. and Sphedanus quadrimaculatus (Thorell 1897) comb. nov. Campostichommides Strand 1911 and Dianpisaura Zhang, Zhu & Song 2004 are recognised as junior synonyms of Dendrolycosa. Nilus lanceolatus Simon 1898 and Pisaura lizhii Zhang 2000 are proposed as junior synonyms of Dendrolycosa robusta Thorell 1895. Four species are described as new: D. bairdi spec. nov. from Laos (male, female), D. duckitti spec. nov. from Laos (male, female), D. sierwaldae spec. nov. from New Guinea (female) and D. yuka spec. nov. from Australia (female). Eight species previously placed in the genera Nilus, Campostichommides Strand 1911, Pisaura Simon 1885 and Dianpisaura Zhang, Zhu & Song 2004, respectively are transferred to Dendrolycosa: D. ornata (Berland 1924) comb. nov. from New Caledonia, D. spadicaria (Simon 1897) comb. nov. from India (nomen dubium), D. bobbiliensis (Reddy & Patel 1993) comb. nov. from India, D. gitae (Tikader 1970) comb. nov. from India, D. inquirenda (Strand 1911) comb. nov. nomen dubium from Indonesia, D. parangbusta (Barrion & Litsinger 1995) comb. nov. from Philippines, D. putiana (Barrion & Litsinger 1995) comb. nov. from Philippines, D. songi (Zhang 2000) comb. nov. from Yunnan, China. Dendrolycosa stauntoni Pocock 1900 is considered a nomen dubium. One species originally described in Dendrolycosa is transferred to the genus Hygropoda: H. gracilis (Thorell 1891) comb. nov. Two species previously placed in the genus Tinus F. O. Pickard-Cambridge 1901 are transferred to Hygropoda: H. sikkimus (Tikader 1970) comb. nov., H. chandrakantii (Reddy & Patel 1993) comb. nov.